2013
DOI: 10.7454/mst.v16i2.1517
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF SIZE AND CRUMB RUBBER COMPOSITION AS A FILLER WITH COMPATIBILIZER PP-g-MA IN POLYPROPYLENE BLENDS AND SIR-20 COMPOUND ON MECHANICAL AND THERMAL PROPERTIES

Abstract: Having been researched the development of thermoplastic elastomer material of polypropylene and natural rubber SIR-20 compound with Crumb Rubber as the filler. Reinforced polypropylene with size 60 mesh with 1 mm, and the composition of the Crumb rubber (30, 40, and 50) wt%. Observed mechanical properties are tensile strength, fracture elongation, Young's modulus, tear strength and impact strength. Thermal properties are analyzed by DSC and DTA/TGA. It is acquired that for the size of 60 mesh crumb rubber tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Another research work applied crumb rubber particles with polypropylene composite and used PPg-MA as a compatibilizer. 20 The mechanical properties were compared with those of rubber composite (SIR20 which is the standard Indonesian rubber). The crumb rubber particles with the size of 0.246 mm and 1 mm were used at loadings of 30, 40 and 50 wt%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research work applied crumb rubber particles with polypropylene composite and used PPg-MA as a compatibilizer. 20 The mechanical properties were compared with those of rubber composite (SIR20 which is the standard Indonesian rubber). The crumb rubber particles with the size of 0.246 mm and 1 mm were used at loadings of 30, 40 and 50 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that filling crumb rubber up to 22% of the basic rubber weight could significantly improve the mechanical properties of the basic rubber. Another research work applied crumb rubber particles with polypropylene composite and used PP‐g‐MA as a compatibilizer 20 . The mechanical properties were compared with those of rubber composite (SIR20 which is the standard Indonesian rubber).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most useful techniques, at least as a starting point, is grinding (particle size reduction) to use the resulting ground tire rubber (GTR) in polymer compounds (blends, composites) as a filler (active or not) or as an impact modifier to improve the elasticity/ductility/toughness of a neat resin (thermoplastic or thermoset). For instance, ground tire rubbers can be introduced into thermoplastic resins to produce thermoplastic elastomers (TPE) [9]. The main matrixes studied so far are polyolefins (polyethylene and polypropylene).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the essential modulus and mechanical strength as well as thermal resistance are low, natural rubber is commonly blended with other materials, one of them is polypropylene (PP). Several studies have reported that blending of natural rubber with PP resulted in characteristic improvement, such as increased thermal stability [1], decreased fracture elongation [2], and increased Young's modulus [3]. However, the NR/PP was found to exhibit low abrasion resistance, tear strength, and high rolling strength, which make it unsuitable for many practical uses of rubber materials, such as tire.…”
Section: Introductionmentioning
confidence: 99%